Oral propranolol in the treatment of proliferating infantile haemangiomas: British Society for Paediatric Dermatology consensus guidelines3. (17th September 2018) - Solman, L.; Glover, M.; Beattie, P.E.; Buckley, H.; Clark, S.; Gach, J.E.; Giardini, A.; Helbling, I.; Hewitt, R.J.; Laguda, B.; Langan, S.M.; Martinez, A.E.; et al.
Summary: Background: Infantile haemangiomas (IH) are the most common vascular tumours of infancy. Despite their frequency and potential complications, there are currently no unified U.K. guidelines for the treatment of IH with propranolol. There are still uncertainties and diverse opinions regarding indications, pretreatment investigations, its use in PHACES (posterior fossa malformations–haemangiomas–arterial anomalies–cardiac defects–eye abnormalities–sternal cleft and supraumbilical raphe) syndrome and cessation of treatment. Objectives: To provide unified guidelines for the treatment of IH with propranolol. Methods: This study used a modified Delphi technique, which involved an international treatment survey, a systematic evidence review of the literature, a face‐to‐face multidisciplinary panel meeting and anonymous voting. Results: The expert panel achieved consensus on 47 statements in eight categories, including indications and contraindications for starting propranolol, pretreatment investigations, starting and target dose, monitoring of adverse effects, the use of propranolol in PHACES syndrome and how to stop treatment. Conclusions: These consensus guidelines will help to standardize and simplify the treatment of IH with oral propranolol across the U.K. and assist in clinical decision‐making. Abstract : Linked Comment: Janmohamed. Br J Dermatol 2018;179 :553–554 . Plain language summary available online